MATERNITY NURSING CARE MANAGEMENT WITH EXCELLENT SERVICE FOR MRS.A WITH SECOND-TRIMESTER HYPERTENSION AT PERA CLINIC, MEDAN TUNTUNGAN DISTRICT NORTH SUMATRA PROVINCE, IN 2025 - Yuniata; Imran Saputra Surbakti; Furi Estie Honez; Laura Fransiska Lumban Gaol; Listra Maretta Br Brahmana; Merdu Zamili; Toga Adi Putra Sinaga (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Background: Hypertension during pregnancy remains a major obstetric complication, contributing significantly to maternal and fetal morbidity and mortality. In the primary care setting, standardized yet empathetic care is essential for early detection and prevention. Objective: This case study aims to implement and analyze a maternity nursing care management model based on "Service Excellence" for Mrs. A, a pregnant woman diagnosed with hypertension during her second trimester. Methods: The study was conducted at Pera Clinic, Medan Tuntungan, North Sumatra, using a longitudinal nursing process approach. This included a comprehensive clinical assessment, nursing diagnosis formulation, evidence-based care planning, implementation, and systematic evaluation. The "Service Excellence" framework focused on professionalism, responsiveness, and empathetic communication. Results: The application of service-excellence nursing care resulted in improved clinical monitoring of blood pressure, enhanced patient health literacy, and high patient satisfaction. Furthermore, the collaborative approach helped in maintaining blood pressure stability and preventing progression toward preeclampsia. Conclusion: This study highlights that professional, collaborative, and responsive nursing services are vital in managing hypertensive disorders in pregnancy. Such a model directly supports the Sustainable Development Goals (SDGs) by contributing to the reduction of maternal mortality through high-quality, patient-centered care